The late medieval English college and its context - Burgess, Clive; Heale, Martin, 1974- (York Medieval Press, 2008)
A wide ranging survey of the medieval secular college and its context. Secular colleges stand as the most characteristic late medieval religious foundation, with hundreds established across fourteenth- and fifteenth-century Europe; but they remain by far the least studied. This volume provides the first scholarly overview of the late medieval college and its place in English religion, society and culture. The contributions survey and reflect the wide influence of the college. They consider the religious, political, intellectual, educational, charitable, musical and artistic contributions of these foundations, and combine detailed case studies with broader surveys placing the English college in its wider British and European context. The volume thus offers an unrivalled introduction to English secular colleges, demonstrating why these foundations were so important to late medieval religion and society. CONTRIBUTORS: CLIVE BURGESS, JEROME BERTRAM, HELEN BROWN, MARTIN HEALE, A.K. MCHARDY, JULIAN M. LUXFORD, P.H. CULLUM, JAMES WILLOUGHBY, MAGNUS WILLIAMSON, ANNE F. SUTTON, WINIFRED A. HARWOOD, DAVID SKINNER--